Removal of priority PAHs from coking wastewater = Usuwanie priorytetowych WWA ze ścieków koksowniczych - Turek, Agnieszka; Włodarczyk-Makuła, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of these tests described in this study was to determine the effectiveness of removing eight aromatic compounds from the list of priority. Tests were carried out using coke produced during wastewater treatment of coke oven gas. The technology research was consisted in introducing into wastewater samples taken with 30% solution of hydrogen dioxide (50 mg/dm3, 100 mg/dm3, 300 mg/dm3, 600 mg/dm3, 900 mg/dm3, 1000 mg/dm3, 2000 mg/dm3).
Keywords: utlenianie; ścieki koksownicze; ścieki przemysłowe; analiza WWA; oxidation; industrial wastewater; analysis of PAHs